Pengaruh Pendidikan Kewirausahaan dan Lingkungan keluarga Terhadap Minat Berwirausaha - Syila Aliffia Sofyan; Raden Roro Suci Nurdianti; Yoni Hermawan (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The research aims to determine the influence of entrepreneurship education and family environment on entrepreneurial interest. This research uses a quantitative approach with the research method being a survey method and the research design being explanatory. The population in this study consists of the 2022 cohort of Economics Education students at Siliwangi University who have enrolled in the entrepreneurship course, totaling 128 individuals. The sampling method used is proportionate stratified random sampling. The data collection technique for this research uses a questionnaire, and the data analysis technique employed is multiple linear regression analysis. The research results indicate that there is a positive and significant influence between entrepreneurship education and entrepreneurial interest, there is a positive and significant influence between the family environment and entrepreneurial interest, and there is a positive and significant influence between entrepreneurship education and the family environment on entrepreneurial interest.